Bis-Tetrazine Fluorogenic (Silicon)-Rhodamine Dyes for Live-Cell Labeling - Sabrina Giofrè; Lukas Schartel; Richard Wombacher; Edward A. Lemke (Journal of the American Chemical Society, 2026)
Abstract Fluorogenic click dyes are valuable tools for biorthogonal labeling, enabling real-time visualization of biomolecules and cellular processes in their native environments. However, achieving efficient quenching and high fluorescence turn-on within a single dye scaffold remains a significant challenge. Herein, we report a class of fluorogenic click dyes based on a structural modification of (silicon)-rhodamines at the amino groups of the xanthene scaffold, resulting in a particularly short linker and a highly optimized quenched state. This modification enables the synthesis of both mono- and bis-functional derivatives. The monofunctional dyes are fully compatible with established click-labeling strategies and display exceptional fluorogenic responses, with fluorescence enhancements of up to 2 orders of magnitude. Notably, the bis-functional derivatives are fluorogenic dyes that exhibit fluorescence turn-on ratios approaching 3 orders of magnitude upon biorthogonal reaction, making them particularly suitable for live-cell applications. We show that the short bis-linker has high potential for anisotropy measurements that can report on protein size and dynamics. We further demonstrate the unique utility of these bis-functional dyes for peptide cyclization, enhancing cellular uptake while enabling real-time visualization. Together, this work introduces a versatile dye class that substantially expands the scope of click chemistry and will advance applications in live-cell imaging as well as studies of protein structure and dynamics.